A study on student's perception on social integration among multi ethnic students at selected public university - Ann Marie, Muniandy (2019)
Social integration is the creation of society for all. It is the mechanism of constructing the ideals, partnerships and organizations dispensable for the origination of such an fairer and immersive civilization, where all individuals, irrespectively of their ethnicity, intercourse idiom or creed can comprehensively workout their liberties and commitments on an equal grounds with others and contribute the society. Social integration has always been overlooked and taken for granted by most our Malaysian citizen, relating to that comes the controversial issue being said publicly and indirectly criticizing each other. Therefore, the purpose of this study is identify the students perception and attitudes towards social integration process and also to examine the ethnic interaction among undergraduate students. The research has been conducted in four different public universities in Malaysia using primary qualitative data as the method.